European Security Defense Identity: A Romanian Perspective - Savu, Mircea (2000)
NATO established the European Security Defense Identity (ESDI) at the 1994 Summit in Brussels. Since then there has been considerable debate on both sides of the Atlantic on the implications of developing ESDI and how to structure it. For fifty years the major focus of European military effort has been through NATO. This effort will continue because NATO has always been a partnership between America and Europe. But the recent events in the Balkans increasingly emphasized that this partnership has become unbalanced. The quality and ability of forces contributed by European nations has not been sufficient set alongside the input of the United States. European states have to shoulder a greater burden for their own security. NATO has opened itself to the East by creating at first the North Atlantic Cooperation Council and in 1994 the Partnership for Peace program and later, the Euro-Atlantic Cooperation Council. In addition the Alliance has remained open to membership of other European countries To date, twelve nations have asked to join NATO and three have already joined the Alliance. In the meantime, the European Union Member states "reactivated" the Western European Union (WEU) in an effort to establish a European Security Defense Identity. Romania has not succeed in convincing NATO that it should be part of the first wave of entrants into the Alliance. In the last days of 1999, Romania has been invited along with other European states to start the negotiations with European Union. From this perspective Romania encouraged a stronger, more capable Europe. So what Romania got from Helsinki Summit, held in December 1999 is a new arrangement for its own security, not as an alternative to NATO, which still remain a strategic goal, but a faster integration into western civilization, economically and militarily.